Women fielding danger: Negotiating ethnographic identities in field research - Huggins, Martha Knisely; Glebbeek, Marie-Louise (Rowman & Littlefield Publishers, 2009)
Keywords: approches et analyses; discipline; ethnographie; genre; identités; méthodologie; point de vue situé; sciences humaines; sciences sociales; éthique

Experiments in knowing: Gender and method in the social sciences - Oakley, Ann (The New Press, 2000)
Ann Oakley came to widespread attention as part of the new school of British feminists to emerge in the 1960s, and has since earned a reputation as one of the most innovative feminist thinkers and social scientists writing today. In Experiments in Knowing, a major new work, Oakley integrates her personal and professional thinking to examine the historical development of methodology in the social and natural sciences, demonstrating how both fields have been subject to a process of "gendering." Oakley not only reconciles the long-standing opposition between the quantitative and the qualitative methods but shows that the experimental and intuitive approaches must be used in tandem to provide a full understanding of any subject of scientific inquiry. Written in accessible language, Experiments in Knowing addresses themes of common interest across such diverse fields as social policy, education, health, and women's studies. Certain to generate considerable debate, it is both a fascinating history of the practice of social science from a feminist perspective, as well as an argument for a new way of thinking about our ways of knowing.
Keywords: 1900-1999; approches et analyses; cours; discipline; europe; fem1000; genre; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sciences sociales; thématiques; théories féministes; épistémologie

Questionnements féministes et méthodologie de la recherche - Ollivier, Michèle; Tremblay, Manon (Collection Outils de recherche, 2000)
La recherche féministe repose-t-elle sur une éthique de la recherche qui lui est propre, Est-elle mieux servi par les méthodes qualitatives que quantitatives ? Comment arrive-t-elle à concilier engagement politique et effort d'élaboration d'un discours vrai sur le monde ? Cet ouvrage présente quelques éléments essentiels de la réflexion féministe actuelle sur la méthodologie de la recherche en sciences humaines et sociales.
Keywords: approches et analyses; canada; cours; cycles supérieurs; discipline; discours; fem1000; fem7000; har4600; justice sociale; méthodologie; point de vue situé; premier cycle; pédagogie; sciences humaines; sciences sociales; thématiques; épistémologie